Electrophysical properties of PMN-PT-PS-PFN:Li ceramics - Skulski, R.; Bochenek, D.; Niemiec, P.; Wawrzała, P.; Suchanicz, J. (Condensed Matter Physics, 2013)
We present the technology of obtaining and the electrophysical properties of a multicomponent material 0.61PMN-0.20PT-0.09PS-0.1PFN:Li (PMN-PT-PS-PFN:Li). The addition of PFN into PMN-PT decreases the temperature of final sintering which is very important during technological process (addition of Li decreases electric conductivity of PFN). Addition of PS i.e., PbSnO₃ (which is unstable in ceramic form) permits to shift the temperature of the maximum of dielectric permittivity. One-step method of obtaining ceramic samples from oxides and carbonates has been used. XRD, microstructure, scanning calorimetry measurements and the main dielectric, ferroelectric and electromechanical properties have been investigated for the obtained samples.